2015
DOI: 10.1039/c5cc05484b
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of TiO2-supported twinned gold nanoparticles by CO treatment and their CO oxidation activity

Abstract: We found that twinned gold nanoparticles (T-AuNPs) are generated at a high probability by CO treatment of TiO2-supported Au(iii) at room temperature. Because of the formation of T-AuNPs, the Au/TiO2 prepared by the CO treatment showed higher catalytic activity for CO oxidation than Au/TiO2 prepared by conventional H2 treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Hence, gold catalysts under the guideline of particle size control can be well designed. Previous studies have also suggested, however, that factors other than particle size such as support effect, cluster size or single atom effect, and crystal structure also greatly contribute to the performance of gold catalysts . In other words, the effect of the catalyst structure is a multi‐dimensional problem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, gold catalysts under the guideline of particle size control can be well designed. Previous studies have also suggested, however, that factors other than particle size such as support effect, cluster size or single atom effect, and crystal structure also greatly contribute to the performance of gold catalysts . In other words, the effect of the catalyst structure is a multi‐dimensional problem.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also suggested, however, that factors other than particle size such as support effect, cluster size or single atom effect, and crystal structure also greatly contribute to the performance of gold catalysts. [17][18][19] In other words, the effect of the catalyst structure is a multi-dimensional problem. If such multi-dimensional problem can be treated within machine learning, further sophisticated catalyst design can be made achievable in principle.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that the exceptional activity of gold nanoparticles for the low-temperature CO oxidation arose from the presence of highly-uncoordinated atoms. Twinning of Au NPs shows higher activity for the CO oxidation reaction than single crystal Au NPs [9,14,15]. The morphology effect by twinning was shown to be independent of the size effect.…”
Section: Introductionmentioning
confidence: 92%
“…For twin NPs, two types of structures are adopted; one is a single twin structure, which has a single grain boundary, and the other is a multiple twin type, which has five-fold twinning. Both types of twin NPs were experimentally observed [13,14]. The single-twin NP has the symmetry of D 3h (hereafter, referred to as "D 3h -NP").…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation